Zonation of a small mammal community within coastal dunes. (5th February 2019) - Rendall, Anthony R.; Cooke, Raylene; White, John G.; Weston, Michael A.
Abstract: Zonation is a dominant feature of coastal ecologies, yet comparatively few studies are available on zonation of ecological assemblages in coastal dunes. Studies of zonation often focus on invertebrate macrofauna in the sub or inter-tidal regions; rarely has zonation of small mammal communities been considered in dunes. In this study we use 10 years of mammal trapping data and show that a diverse small mammal community was present within a coastal dune system. Nine species were captured within the dune, only one of which was introduced. The invasive house mouse was limited to a narrow band above the beach/dune interface, while the native small mammal assemblage dominated in the rest of the dune field. This clear zonation may result from habitat preference, interspecific competition, predation, species-specific predator risk tolerances, marine or beach subsidies or a combination of these influences. We demonstrate the conservation value of dune systems and highlight the presence of zonation within a mobile small mammal community.